1993
DOI: 10.1113/jphysiol.1993.sp019626
|View full text |Cite
|
Sign up to set email alerts
|

The role of the kidney in canine blood pressure control: direct assessment of the closed‐loop gain.

Abstract: SUMMARY1. The feedback control of arterial blood pressure by the kidney in the range of hours was investigated in resting, conscious foxhounds.2. A servo-control device (connected to an aortic occlusive cuff implanted above both renal arteries) was used to maintain a constant pressure difference of 20 mmHg between aortic pressure measured proximal (mean arterial blood pressure: MAP) and distal (renal artery pressure: RAP) to the aortic cuff.3. Protocol 1 (n = 6) served as a 4 h time control without interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…The answer is both "yes" and "no." It is "no" because of its slow time constant relative to other systems that control sodium balance and blood pressure (36,40,43,72). Thus, even though any change in blood pressure certainly can begin changing urine output within minutes, quicker-acting systems normally are able to match sodium excretion to intake before there is a significant change in blood pressure.…”
Section: Using Sodium Balance As the Framework For Long-term Blood Prmentioning
confidence: 97%
See 1 more Smart Citation
“…The answer is both "yes" and "no." It is "no" because of its slow time constant relative to other systems that control sodium balance and blood pressure (36,40,43,72). Thus, even though any change in blood pressure certainly can begin changing urine output within minutes, quicker-acting systems normally are able to match sodium excretion to intake before there is a significant change in blood pressure.…”
Section: Using Sodium Balance As the Framework For Long-term Blood Prmentioning
confidence: 97%
“…Other blood pressure control systems have measurable, finite feedback gains (6,14,43,72,78). This means they can correct a blood pressure disturbance only a certain proportion of the way back to normal.…”
Section: Integration Of Blood Pressure Control Systemsmentioning
confidence: 99%
“…It has previously been shown that when RPP is reduced to 70 mmHg, it takes 5 min before renal venous plasma renin activity is maximal (25). After 20 min of reduced RPP to ϳ80 mmHg, a 400% increase in arterial plasma renin activity (PRA) was found (30).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the renin‐angiotensin system (RAS) to the maintenance of mean arterial blood pressure (MABP) becomes apparent when it is strongly stimulated by sodium deprivation (Johnson & Davis, 1973; Fray et al 1977; Kopelman et al 1983) or during pathophysiological conditions which provoke major circulatory disturbances such as haemorrhage (Brough et al 1975; Kopelman et al 1983). More recently, a continuous tonic influence, as evidenced by a fall in MABP after angiotensin converting enzyme (ACE) inhibition (MacGregor et al 1981; Kopelman et al 1983; Ehmke et al 1987; Hasser & Bishop, 1988; Persson et al 1993), has also been observed under physiological conditions. This tonic effect of the RAS on the level of MABP appears to be controlled, at least in part, by the pressure‐dependent mechanism of renin release, for the following reasons.…”
mentioning
confidence: 99%
“…(2) In conscious dogs, the level of arterial plasma renin activity (PRA) was found to be strongly dependent on the actual difference between MABP and threshold pressure, with higher PRA values being present when MABP was closer to the threshold pressure (Ehmke et al 1987). (3) When MABP was artificially reduced to below the threshold pressure by inducing a constant pressure reduction between the suprarenal aortic and the renal arterial blood pressure (RABP) in conscious dogs, both aortic and renal arterial pressure rose within 2 h until RABP was almost completely restored (Persson et al 1993). Therefore, the pressure‐dependent mechanism of renin release might very well participate in the buffering of the spontaneous blood pressure variability.…”
mentioning
confidence: 99%